Pilonidal Sinus of the Scalp: a Case Report and Review of the Literature - Olcay Ak Nalbant; Erdem Nalbant (Balkan Medical Journal, 2011)
A 31-year-old man presented with a twenty-year history of a slowly growing nodule on his scalp in the postauricular area. The lesion was excised and with the clinical and histological findings, it was diagnosed as a pilonidal sinus. The purpose of this review is to report the unusual occurrence of a pilonidal sinus on the scalp and review the literature regarding especially this location.